Hybridizing consumer behavioural approaches on agrifood markets: Attitudes, judgements and choices - Salazar-Ordóñez, Melania; Rodríguez-Entrena, Macario (Spanish Journal of Agricultural Research, 2019)
The attitudinal approach, represented by the Theory of Reasoned Action and, subsequent, Theory of Planned Behaviour, and the judgements and choices – also called decision – approach, rendered by the Classical Utility Economic Theory, are the two mainstream frameworks to explain consumer behaviour. The former explains consumer behaviour based on beliefs and behavioural intentions, and the latter on products’ attributes and prices. Both are criticized by having drawbacks, which may limit their explicative and predictive power, such as the attitude-behaviour or intention-behaviour gap in the former, and both the divergence between monetary assessment and predicted utility as well as the failures to maximize the utility of the choices in the latter. Our aim was to assess the potentiality of a hybrid approach which integrates instruments from both theories in order to unravel consumer behaviour in agri-food markets. The empirical research was performed using a daily agri-food product under volitional control, olive oil, and variance-based structural equation modelling by means of the Partial Least Squares (PLS) technique, collecting data from consumers in Southern Spain. The results show there are key factors from both approaches such as attitude, expected outcomes, and socioeconomic features, which makes us conclude that it is necessary to move forward on the convergence and integration of different theories. Indeed, testable knowledge must be produced which has meaningful implications for predicting behaviours in consumption.